Research on Social Skills in Indonesia: A Systematic Literature Review in Reputable Journals - Usman, Ali; Munandar, Kukuh; Wadiono, Gandu; Wulandari, Siti; Laros, Vizza Az Zahra Al (FKIP Universitas Lampung, 2023)
Research on social attitudes in Indonesia: A systematic literature review in reputable journals. Social skills are important attention to because life's challenges are increasingly complex. Objectives 1) The distribution of social skills in various fields of science, 2) Trends in social skills in the social sciences, 3) Which countries have the most articles about social skills, and 4) What important information is contained in social skills? The method is a Systematic Literature Review (SLR), with parameters: 1) Publication in 2018-2023, 2) English, 3) Accessibility, and 4) Social skills theme. Results: 1) Social skills articles are spread across various fields of science; 2) Trends in articles in the field of social sciences experience fluctuations; 3) Indonesia reviews many articles about social skills and collaboration between countries; 4) Important information, namely models, methods and collaborative learning media can encourage the development of social skills. Conclusion, social skills play an important role in forming the ability to collaborate and develop students' character in the learning context. Keywords: instructional media, learning methods, learning model, social skilDOI: http://dx.doi.org/10.23960/jpp.v13.i3.202329